2017
DOI: 10.7897/2277-4343.08258
|View full text |Cite
|
Sign up to set email alerts
|

An Open Labeled, Randomized, Parallel Arms, Clinical Trial to Evaluate Sedative Effect of Leaves of Beejapura (Citrus Medica Linn.) and Rhizome of Jatamansi (Nardostachys Grandiflora) in Anidra (Primary Insomnia)

Abstract: Primary insomnia is a major health issue with a bearing on the morbidity, health related quality of life. Pharmacologic treatment for insomnia has been shown to be associated with significant side effects; hence, it is need to search safe and effective remedies from natural sources. Powder of Beejapura (Citrus medica Linn) leaves with honey has been indicated to induce sleep in classical text of Ayurveda. Keeping this in view, open labelled, randomised parallel arm clinical trial was planned to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…[64] A randomized controlled trial demonstrated that GS played a crucial role in sleep induction and sleep maintenance for patients with insomnia. [65] We identified 54 bioactive ingredients of core herbs treating insomnia, including β-sitosterol, stigmasterol, cryptotanshinone, cavidine, and baicalein. β-Sitosterol is derived from BX, XKC, and BH; stigmasterol comes from BH and BX; canadine is found in YHS; cryptotanshinone is present in GS; cavidine is found in BX and YHS; baicalein is derived from BX and HH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] A randomized controlled trial demonstrated that GS played a crucial role in sleep induction and sleep maintenance for patients with insomnia. [65] We identified 54 bioactive ingredients of core herbs treating insomnia, including β-sitosterol, stigmasterol, cryptotanshinone, cavidine, and baicalein. β-Sitosterol is derived from BX, XKC, and BH; stigmasterol comes from BH and BX; canadine is found in YHS; cryptotanshinone is present in GS; cavidine is found in BX and YHS; baicalein is derived from BX and HH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 64 ] A randomized controlled trial demonstrated that GS played a crucial role in sleep induction and sleep maintenance for patients with insomnia. [ 65 ]…”
Section: Discussionmentioning
confidence: 99%